PERANCANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEB PADA SMK N 6 MUARO JAMBI - Adi Saputra; Mulyadi Mulyadi; Martono Martono (Jurnal Ilmiah Media Sisfo, 2014)
New admissions system that runs at SMK N 6 Muaro currently still using a manual system. Applicant must must come directly to the school to find out the registration information, the registration process to see the announcement of the selection results. This resulted in frequent queues at school at the time of admission schedule. From the problems the author offers a solution with acceptance of new students information systems that are built using web-based programming language that is accessible to potential students through the Internet. System development method used is waterfall. With the web-based admission system acceptance process will become easier and faster. Additionally the report can be created automatically by the system. But this system can not send notifications using text messages so for further research in order to develop a notification system via short messages or SMS. Keywords: Design, Information system, New Admissions, Web